Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
so 3 times (3 times) the sum of (+) a number and 4 (x,4) is equal to (=) five times the number (5x) decreased by 2 (-2)
the equation would be 3(x+4)=5x-2
so if we solve we get
3x+12=5x-2
12=2x-2
10=2x
5=x
the equation would be 3(x+4)=5x-2
so if we solve we get
3x+12=5x-2
12=2x-2
10=2x
5=x
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.